PENGARUH MODEL PROBLEM BASED LEARNING (PBL) DIPADU MIND MAP TERHADAP KREATIVITAS DALAM MEMECAHAN MASALAH PADA KONSEP PENCEMARAN LINGKUNGAN - Susanti, Novi Tri; Hindriana, Anna Fitri; Satianugraha, Haruji (Universitas Galuh, 2019)
This study aim to determine the effect of Problem Based Learning (PBL) models in mind map integration to creativity of problem solving in the environmental pollution concept of graders X. The method used is a Quasi-experimental design form Nonequivalent Control Group Design (pretest- posttest). The study population is all the students of graders X academic year 2017/2018 as many as 9 classes with the number of 360 students. The sample used was 80 students from two classes as an experimental class and a control class. Sampling was done by Cluster Random Sampling technique. Instruments used include test descriptions, questionnaires and teacher observation sheets. The results of the analysis of the test descriptions creativity in problem solving obtained results of hypothesis testing (t test) i.e. 20.5 t count > t table of 2.66 means that Ho refused and Hi accepted, it means PBL learning models in Mind Map integration effect on creativity in problems solving. This is indicated by an increase in the average score on each indicator of creativity in problem solving in which students are able to grow various ideas, enrich ideas, add or detail the details of an idea and determine the truth to solve the problems. From the analysis of questionnaire data showed an interest in learning to use the PBL modela in Mind map integration, students agreed that if the model of PBL in Mind map integration may be easier to learn about the concept of Environmental Pollution. In addition, students also agreed that if the PBL models in Mind map integration effect on creativity in problems solving. The results showed that there was a significant influence between learning using PBL models in Mind map integration those not using the learning models to creativity in problems solving in the concept of environmental pollution of graders X.